Punitive consequences of being a minority male: an analysis exploring intersectionality, racial/ethnic threat, and sentencing outcomes - Okafor, Porche’ A.W. (Psychology, crime & law, 2026)
Decades of sentencing research have demonstrated that there are disparities in sentencing outcomes based on race and ethnicity, sex, age, and racial/ethnic contexts, net of legally relevant factors. These findings have led to concerns around fairness and justice of the law for all citizens, especially for minority males of various ages. However, little is known about how the combined effects of being a minority male of various ages across contexts influence disparities in sentencing. The purpose of the current research is to address the inattention of analyzing the intersection of individual-level characteristics across racial and ethnic contexts and how these effects contribute to sentencing disparities. To test the hypotheses, the current study uses 2010–2017 Florida Sentencing Guidelines data, combined with county-level data from the 2010 United States Census. The results suggest that some minority men of various ages receive a punishment penalty. Moreover, some minority men of various ages receive harsher sentencing outcomes when sentenced in areas with a growing racial/ethnic presence. Overall, the findings lend some support to the notion of intersectionality, minority threat and punitive outcomes.